Enhancing men's awareness of testicular diseases (E-MAT) feasibility trial: Protocol for a mixed method process evaluation [version 2; peer review: 2 approved] - Janas M. Harrington; Josephine Hegarty; Frances Shiely; Gillian Shorter; Martin Davoren; Megan McCarthy; Eoghan Cooke; David Murphy; Mohamad M. Saab; Billy O'Mahony (HRB Open Research, 2023)
Background: Testicular cancer (TC) is the most common malignancy in men under 50 years. Athletes are particularly at risk of testicular trauma and diseases. Experiencing negative testicular symptoms does not necessarily imply that men seek help. Men’s awareness of testicular diseases is often lacking and their intention to seek help for testicular symptoms is sub-optimal. The use of virtual reality (VR) may be effective in promoting men’s awareness of testicular diseases. The Enhancing Men's Awareness of Testicular diseases (E-MAT) feasibility trial aims to test the effect of E-MATVR (intervention; interactive experience using virtual reality [VR]) compared to information delivered Electronically E-MATE (control; same information as E-MATVR delivered as plain text and images) on testicular knowledge, and testicular self-examination among male athletes affiliated with a national sports organisation. The overall aim of this mixed method process evaluation will be to describe (i) the experiences of participants and key stakeholders (e.g., researchers); (ii) the perceived effectiveness of intervention components; (iii) acceptability of the feasibility trial and intervention procedures; (iv) the relationship between implementation, mechanisms, and context; and (v) the barriers and facilitators to support effective conduct of a future definitive trial.   Methods: This mixed method process evaluation will use a descriptive realist evaluation. Quantitative data will be gathered using a usability and satisfaction survey, in addition to fidelity checks during intervention delivery. Quantitative data will be analysed using descriptive and inferential statistics. Qualitative data will be gathered from semi-structured interviews and focus groups with participants and key stakeholders to investigate their experiences of E-MATVR and E-MATE, and explore areas for improvement. Thematic analysis of transcripts will be conducted. Conclusions: This process evaluation will provide an in-depth understanding of how the interventions worked within this cohort and lessons for a future definitive trial.